The Tasks of Translatability - Thomas, Peter (International Gramsci Journal, 2023)
While Walter Benjamin’s essay “The Task of the Translator” has long been considered one of the fundamental texts of translation theory, Gramsci’s important remarks on the question of translatability were not noted in the canonical studies of the history of translation theory nor, for a long time, in Gramscian studies themselves. Nevertheless, the notion of translatability plays a crucial role in the general economy of the Prison Notebooks. This paper proposes a dialogical reading ‘against the grain’ of three constellations of some of Gramsci and Benjamin’s key concepts regarding the nature of translation and its philosophical presuppositions and implications. These constellations revolve around the Gramscian notions of hegemony, of translation between ethico-political contexts, and of reciprocal translatability; they are here read through the Benjaminian notions of translation as generative of the ‘afterlife’ of a literary work, as participating in a ‘pure language’ that functions as translation’s ‘horizon’, and as constituting an ‘echo’ of the original text in a new linguistic and historical context. The encounter of Gramsci and Benjamin is not only on their points of clear convergence but also on those points where they might seem to diverge: this forms the basis for translation and transposition between their respective thought-worlds – a translation that at the same time represents an attempt to open their works up to their immanent transformation.